Spring sea ice photosynthesis, primary productivity and biomass distribution in eastern Antarctica, 2002-2004 - McMinn, A; Ryan, KG; Ralph, PJ; Pankowski, A (2007)
While it is known that Antarctic sea ice biomass and productivity are highly variable over small spatial and temporal scales, there have been very few measurements from eastern Antarctic. Here we attempt to quantify the biomass and productivity and relate patterns of variability to sea ice latitude ice thickness and vertical distribution. Sea ice algal biomass in spring in 2002, 2003 and 2004 was low, in the range 0.01-8.41 mg Chl a m-2, with a mean and standard deviation of 2.08 ± 1.74 mg Chl a m-2 (n = 199). An increased concentration of algae at the bottom of the ice was most pronounced in thicker ice. There was little evidence to suggest that there was a gradient of biomass distribution with latitude. Maximum in situ production in 2002 was approximately 2.6 mg C m-2 h-1 with assimilation numbers of 0.73 mg C (mg Chl a)-1 h-1. Assimilation numbers determined by the 14C incubations in 2002 varied between 0.031 and 0.457 mg C (mg Chl a)-1 h-1. Maximum fluorescence quantum yields of the incubated ice samples in 2002 were 0.470 ± 0.041 with Ek indices between 19 and 44 μmol photons m-2 s-1. These findings are consistent with the shade-adapted character of ice algal communities. In 2004 maximum in situ production was 5.9 mg C m-2 h-1 with an assimilation number of 5.4 mg C (mg Chl a)-1 h-1. Sea ice biomass increased with ice thickness but showed no correlation with latitude or the time the ice was collected. Forty-four percent of the biomass was located in bottom communities and these were more commonly found in thicker ice. Surface communities were uncommon. © 2006 Springer-Verlag.